#gagalkanomnibuslaw movement: How Simulacra Sparks Mass Action - Oktavianingtyas, irmawati; Wono, Hilda Yunita; Gusfa, Henni (Universitas Bunda Mulia, 2023)
The hash-tag #gagalkanomnibuslaw used by the twitter